Editorial. Special Issue - Abdul Manaf, Nor Faridah; Musa, Muhammad Adli (Penerbit Universiti Sains Malaysia, 2019)
This special issue of KEMANUSIAAN the Asian Journal of Humanities comprises of nine articles that discuss various topics related to humanities and religiosity, focusing mainly on Islamic thought and religious ideals. The first article ventures to uncover an extremely crucial aspect that was often neglected in the treatment of Islamic scriptures. It attempts to study the possibility of applying the art and science of voice intonation when reading the scriptures, particularly the ḥadīth. This study not only looks at how voice intonation could help identify various linguistic and prosodic elements as well as styles, but also how it could significantly affect the understanding of a certain ḥadīth. The preliminary analysis of this study has successfully raised this problem for further scholarly endeavours in religion and humanity studies. The second article explores the linkages between Islamic spirituality and the instruction of science. This explorative study on Islamic spirituality and science demonstrates that the inclusion of spirituality in the teaching of natural sciences is beneficial for students as it will help them connect their spiritual experience with the content of science, use their innate abilities to further understand nature, and learn how to grasp the meaning of things. The third article, on the other hand, aims at delineating Islamic position with regard to the conflict between the habituation method and the moral autonomy. The study shows that habituation method is incompatible with the goal of Islamic education, which is the rational growth and development of the youth. Hence, it cannot be accepted in Islamic moral education. The fourth article examines a Persian travelogue written by Ḥājj Sayyāḥ, entitled Safarnāmaḥ-i Ḥājj Sayyāḥ bih Farang, which presents a journey of escaping the captivity of ignorance and heading towards absolute freedom by disciplining the soul in a sufi way. Moving to a modern application of Islamic thought, the fifth article examines the issue of Islamic governance from an epistemological point of view as inspired by the general theory of Maqāṣid al-Sharīʿah. The study utilises an “inductive qualitative methodology” (istiqrā’) to explore some conceptual frameworks and critically analyse the texts from authentic Islamic sources. The sixth article, however, invites the readers to explore the past. It analyses the structure of authorities and syncretic practices related to the development of socio-political and cultural-religious environment in South East Asia prior to the spread of Islam in the region. The seventh article not only reveals that Islamic movements played a very significant role in reforming da‘wah work, but also proves that the differences in political ideology were not a major obstacle for Islamic movements in developing da‘wah work in the country. The eighth article, interestingly, parades the life-changing experience of two Westerners’ conversion to Islam based on their autobiographies. In his autobiography The Road to Mecca (1954), Leopold Weiss aka Muhammad Asad, a Jewish convert to Islam narrates vi the road that took him to Islam. Meanwhile, Kristiane Backer, an MTV celebrity presenter who converted to Islam wrote an autobiography entitled From MTV to Mecca: How Islam Inspired My Life (2012). The ninth and final article in this issue assesses the underlying reasons for the sinicization of Chinese Muslims apart from the obvious political necessity of the Chinese imperial government, and the effects of the process on the Muslim community. This paper utilises qualitative and library research methods to look at various factors which contributed to the sinicization of Muslims in China and gives attention to the stimulus for synthesis byThis paper utilises qualitative and library research methods to look at various factors which contributed to the sinicization of Muslims in China and gives attention to the stimulus for synthesis by Muslim intellectuals and scholars.. The findings of this paper indicate that one of such lasting impacts of sinicization is the formation of the Gedimu School which was essentially the synthesis of Chinese and Islamic ideas and traditions.